Registration of 'S13‐3851C' soybean as a high‐yielding conventional cultivar with high oil content and broad disease resistance and adaptation. Issue 1 (27th September 2021) - Chen, P.; Shannon, G.; Scaboo, A.; Crisel, M.; Smothers, S.; Clubb, M.; Selves, S.; Vieira, C. C.; Ali, M. L.; Lee, D.; Nguyen, H. T.; Li, Z.; et al.
Abstract: 'S13‐3851C' (Reg. no. CV‐541, PI 698653) is an early maturity group IV (relative maturity 4.4) conventional soybean [ Glycine max (L.) Merr.] cultivar released by the University of Missouri–Fisher Delta Research Center Soybean Breeding Program. It was developed from a conventional breeding scheme focusing on parental traits including high oil content, multiple disease resistance, and high yielding potential. S13‐3851C has purple flowers, light tawny pubescence, tan pod wall, and indeterminate growth habit. Seeds of S13‐3851C have a black hilum and intermediate seed luster, with 230.8 g kg −1 of oil and 404.1 g kg −1 of protein content on a dry‐weight basis. S13‐3851C is resistant to stem canker, sudden death syndrome, charcoal rot, and Phytophthora root rot. S13‐3851C showed high yield potential and broad adaptability in 113 environments across 12 states, yielding 102% of the check average and 103% of the test average in Missouri and other southern states during the testing period (2014–2018). Core Ideas: Early maturity group provides flexibility for growers in the southern United States. 'S13‐3851C' is a non‐GMO cultivar for premium incentives and specialty markets. High‐oil cultivar supports the ever‐growing demand for vegetable oil. Multiple disease resistances creates yield security across diverse yield‐limiting factors. Yield potential was determined by high performance and stability across 113 environments.